Analysis of sociological aspects of information security using the HAIS-Q model - Jevtić, Nenad; Raut, Jelena (Sociološki pregled, 2024)
The aim of the paper is to research the sociological aspects of information security through the HAIS-Q model, at the Faculty of Engineering Management. The research was conducted anonymously, within a time frame of four months, on a sample of 179 respondents. The HAIS-Q model is built from seven focus groups, which pervade the variables of knowledge, attitudes and behaviours, while the subject research is focused on the focus area “use of the Internet”. By analyzing the variables with the lowest scores in one of the seven focus areas of this model, gaps in information security awareness among employees are explored. The paper highlights the implications of these deficiencies for organizational security and information protection, with an emphasis on the importance of improving the variables with the lowest scores. Through a comprehensive consideration of the sociological dimensions of information security, this paper contributes to a better understanding and management of this important field, emphasizing its importance in today’s digital age.